Border and Behind-the-Border Trade Barriers and Country Exports - Sadikov, Azim (IMF Working Papers; Working Paper, 2007)
How do signatures required for exporting and business registration procedures affect the volume and composition of country's exports? To answer this question, I develop a model where a country can export two types of products: differentiated and homogeneous. I show that export signatures and registration procedures reduce overall exports by increasing transaction costs. The impact, however, varies across goods according to the product's degree of differentiation- the lack of price data on differentiated products due to their heterogeneity makes them more sensitive to export signatures. Regressions show that each extra signature exporters have to collect before a shipment can take place reduces aggregate exports by 4.2 percent. The impact is large, equivalent to raising importer's tariff by 5 percentage points. Furthermore, each signature lowers exports of differentiated products by 4-5 percent more than exports of homogeneous goods. I find evidence that business registration procedures affect exports of differentiated products only.